Effectiveness of Virtual Reality Technology to teach Gen Z students about Construction Safety: A Pilot Study (International Journal of Scientific Research and Management (IJSRM), 2019)
This pilot study was conducted to investigate the effectiveness of using Virtual Reality (VR) technologies to teach the "Generation Z" (GenZ) students about construction safety as part of the Construction Science and Management (CSM) program at Tuskegee University. Research shows that the "Technology Generation" or GenZ students are not satisfied with the traditional pedagogical methodology; rather they demand new hands-on tech-heavy immersive learning experience. In this direction, Virtual Reality is propelling profound technological renovation within the practice of Architecture, Engineering, and Construction (A/E/C) industry allowing for a new pedagogical approach. In this approach, students learn from a 3D dimensional smart environment to help identify the construction safety challenges, instead of going to the potentially dangerous construction sites. This approach has been proven to positively influence construction education in many ways, including enhanced awareness and hazards recognition, in general. This research aimed to test this theory to teach GenZ students enrolled at the CSM program at Tuskegee University. For this study, GenZ students were first exposed to traditional 2D teaching aid demonstrating construction hazards and then the multiple Virtual Reality (VR) serious games. Their response was recorded through written reports, oral interviews and a survey followed by a comparative analysis between 2D visual aid and VR technologies to test the theory as mentioned earlier. These results indicated that the GenZ students greatly welcomed VR Construction Safety exercises more than traditional 2D visual aids and were interested in exploring more.